Phytochemical profile and anti-inflammatory activity of the hull of γ-irradiated wheat mutant lines (Triticum aestivum L.) - Park, Jisu; Kil, Yun-Seo; Ryoo, Ga-Hee; Jin, Chang Hyun; Hong, Min Jeong; Kim, Jin-Baek; Jung, Chan-Hun; Nam, Joo-Won; Han, Ah-Reum (Frontiers in Nutrition, 2023)
Wheat (Triticum aestivum Linn.; Poaceae) is the second most cultivated food crop among all global cereal crop production. The high carbohydrate content of its grains provides energy, multiple nutrients, and dietary fiber. After threshing, a substantial amount of wheat hull is produced, which serves as the non-food component of wheat. For valorization of these by-products as a new resource from which functional components can be extracted, the hull from the seeds of cultivated wheat mutant lines bred after γ-irradiation were collected. Untargeted metabolite analysis of the hull of original cultivar (a crossbreeding cultivar, Woori-mil × D-7) and its 983 mutant lines was conducted using ultra-performance liquid chromatography-electrospray ionization quadrupole time-of-flight mass spectrometry technique. A total of 55 molecules were tentatively identified, including 21 compounds found in the Triticum species for the first time, and 13 compounds not previously 2 This is a provisional file, not the final typeset article described. Among them, seven flavonolignans with a diastereomeric structure, isolated as single compound from the hull of T. aestivum in our previous study, were used as the standards in the metabolite analysis. The differences in their collision cross section values were shown to contribute to the clear distinction between tricine-lignan stereoisomers. To select functionally active agents with anti-inflammatory activity among the identified compounds, the wheat hull samples were evaluated for their inhibitory effect on nitric oxide production in lipopolysaccharide-stimulated RAW 264.7 cells. As a result of multivariate analysis based on the results of chemical and biological profiles of the wheat hull samples, 10 metabolites were identified as key markers, contributing to the distinction between active and inactive mutant lines. Considering that one of the four key markers attributed to anti-inflammatory activity has been identified to be a flavonolignan, the wheat hull could be a valuable source of diverse tricin-lignan type compounds and used as a natural health-promoting product in food supplement.